FILLING DESIGN AND OPTIMIZATION OF AUTOMOBILE SEAT CROSSBEAM BASED ON ALUMINUM FOAM COMPOSITE STRUCTURE - ZHANG YuanRui; WANG GaoFei; ZHANG YongLiang; ZHENG ZhiJun; YE Jian; QU Yuan; YU JiLin (Jixie qiangdu)
Automobile seat crossbeams play an important role in ensuring the living space of passengers in a collision accident. The reasonable filling design may effectively improve the safety performance of automobiles. Based on the characteristics of high specific energy and light weight of aluminum foam, three different kinds of composite structure composed of foamed aluminum and thin-walled steel pipe were designed and filled into automobile seat crossbeams. The bending and compressive properties of the filled seat crossbeams under three-point bending and axial compression were studied by finite element simulation, and then the best filling scheme was optimized. The results show that the bending and axial bearing capacity of the filled seat crossbeam are improved by 193.6% and 241.4% respectively compared with the original one, and the effectiveness of filled seat crossbeams to improve the crashworthiness of vehicle is proved by the side impact simulation.